2002
DOI: 10.1111/j.1574-6941.2002.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of microbial PCB dechlorination by chlorobenzoates, chlorophenols and chlorobenzenes

Abstract: We investigated the effects of chlorobenzoates (3-, 2,3-, 2,4-, 2,5-, 2,3,5- and 2,4,6-chlorobenzoate), chlorophenols (2,3-, 3,4-, 2,5-, 2,3,6- and penta-chlorophenol), and chlorobenzenes (1,2-, 1,2,3-, 1,2,4- and penta-chlorobenzene) on polychlorinated biphenyl (PCB) dechlorination and on the enrichment of PCB-dechlorinating microorganisms. When the natural microbial populations eluted from St. Lawrence River sediments were enriched with each of the 15 haloaromatic compounds (HACs) in PCB-free sediments, PCB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Wu et al found that halopriming with 2,6-BB increased the cell density of OHRB, leading to increased dechlorination rates . Halogenated benzoates and other halogenated aromatic compounds (e.g., chlorobenzenes and chlorophenols) have also been used as haloprimers for PCB dechlorination. , The range of haloprimers was later expanded to include pentachloronitrobenzene, which could better stimulate increased dechlorination of weathered PCBs than tetrachlorobenzene . Chlorinated ethenes have been utilized to scale up non- Dehalococcoides OHRB as bioamendment for PCB dechlorination in mesocosms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al found that halopriming with 2,6-BB increased the cell density of OHRB, leading to increased dechlorination rates . Halogenated benzoates and other halogenated aromatic compounds (e.g., chlorobenzenes and chlorophenols) have also been used as haloprimers for PCB dechlorination. , The range of haloprimers was later expanded to include pentachloronitrobenzene, which could better stimulate increased dechlorination of weathered PCBs than tetrachlorobenzene . Chlorinated ethenes have been utilized to scale up non- Dehalococcoides OHRB as bioamendment for PCB dechlorination in mesocosms.…”
Section: Introductionmentioning
confidence: 99%
“…Although halopriming can be used to increase the biomass of OHRB and may induce genes required for dehalogenation, a significant lag period (from 4 months to 1 year) in PCB dechlorination activity remains. Several studies have demonstrated the initiation of PCB dechlorination following halopriming occurs only after the concentration of the haloprimer was reduced past a critical threshold. , Furthermore, most of the effective electron acceptors thus far applied as haloprimers are halogenated aromatic compounds, the release of which into the environment is generally hazardous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosurfactant amendment can be achieved through the in situ enrichment of surfactant‐producing microorganisms or a direct application of prepared surfactants. Combined with the direct on‐site selective enrichment of dechlorinating populations or an application of selected dechlorinators enriched in mass culture [32], surfactant application can maximize reductive dechlorination of PCBs to the extent that the final products can be mineralized readily by aerobic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…One promising strategy to overcome these limitations may be the addition of more bioavailable alternative compounds. ‘Priming’ by organohalogens, such as brominated biphenyls or halogenated benzoates, has been used previously to stimulate certain patterns of polychlorinated biphenyls (PCB) dechlorination (VanDort et al ., 1997; Deweerd and Bedard, 1999; Wu et al ., 1999), as well as selectively enrich distinct groups of PCB dechlorinators (Wu et al ., 1999; Cho et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%